Osteoarthritis of the hip joint and acetabular dysplasia in women. Issue 3 (March 1995) - Smith, R W; Egger, P; Coggon, D; Cawley, M I; Cooper, C
Abstract : OBJECTIVE–To investigate the suggestion that osteoarthritis (OA) of the hip joint is often caused by subclinical acetabular dysplasia among elderly British women. METHODS–We examined 393 hip joints from the radiographs of a sample of women aged 60-75 years undergoing intravenous urography. Acetabular dysplasia was assessed using measurements of the centre-edge (CE) angle and acetabular depth (AD), which are both reduced in this condition. OA was assessed using an overall grade based on the Kellgren and Lawrence system and by measurement of minimum joint space (MJS). RESULTS–MJS was the more repeatable measure of OA, and showed a strong correlation with overall grade (Spearman rank correlation coefficient rs = -0.61, p < 0.01). MJS was significantly negatively correlated with CE angle (Pearson correlation coefficient r = -0.25, p < 0.001) and AD (r = -0.11, p < 0.05). Consistent with these findings, there was a weak but significant positive correlation between overall grade of OA and one of the two measures (CE angle) of acetabular dysplasia. CONCLUSIONS–These results do not support the hypothesis that mild degrees of acetabular dysplasia account for a substantial proportion of hip OA in elderly women. Changes in hip joint geometry as a result of OA may be responsible for the weak negative association observed.